Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Ask your questions and receive precise answers from experienced professionals across different disciplines. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
To solve for the value of [tex]\( (f - g)(2) \)[/tex] given the functions [tex]\( f(x) = 3x^2 + 1 \)[/tex] and [tex]\( g(x) = 1 - x \)[/tex], we will follow these steps:
1. Evaluate [tex]\( f(2) \)[/tex]:
- Substitute [tex]\( x = 2 \)[/tex] into the function [tex]\( f(x) \)[/tex]:
[tex]\[ f(2) = 3(2)^2 + 1 \][/tex]
- Calculate the square of 2:
[tex]\[ 2^2 = 4 \][/tex]
- Multiply 4 by 3:
[tex]\[ 3 \times 4 = 12 \][/tex]
- Add 1 to 12:
[tex]\[ 12 + 1 = 13 \][/tex]
So, [tex]\( f(2) = 13 \)[/tex].
2. Evaluate [tex]\( g(2) \)[/tex]:
- Substitute [tex]\( x = 2 \)[/tex] into the function [tex]\( g(x) \)[/tex]:
[tex]\[ g(2) = 1 - 2 \][/tex]
- Calculate the subtraction:
[tex]\[ 1 - 2 = -1 \][/tex]
So, [tex]\( g(2) = -1 \)[/tex].
3. Calculate [tex]\( (f - g)(2) \)[/tex]:
- To find [tex]\( (f - g)(x) \)[/tex], we subtract [tex]\( g(x) \)[/tex] from [tex]\( f(x) \)[/tex]:
[tex]\[ (f - g)(x) = f(x) - g(x) \][/tex]
- Substitute [tex]\( x = 2 \)[/tex]:
[tex]\[ (f - g)(2) = f(2) - g(2) \][/tex]
- Use the values we found:
[tex]\[ (f - g)(2) = 13 - (-1) \][/tex]
- Simplify the expression:
[tex]\[ 13 + 1 = 14 \][/tex]
Therefore, the value of [tex]\( (f - g)(2) \)[/tex] is [tex]\( 14 \)[/tex].
So, the correct answer is:
[tex]\[ 14 \][/tex]
1. Evaluate [tex]\( f(2) \)[/tex]:
- Substitute [tex]\( x = 2 \)[/tex] into the function [tex]\( f(x) \)[/tex]:
[tex]\[ f(2) = 3(2)^2 + 1 \][/tex]
- Calculate the square of 2:
[tex]\[ 2^2 = 4 \][/tex]
- Multiply 4 by 3:
[tex]\[ 3 \times 4 = 12 \][/tex]
- Add 1 to 12:
[tex]\[ 12 + 1 = 13 \][/tex]
So, [tex]\( f(2) = 13 \)[/tex].
2. Evaluate [tex]\( g(2) \)[/tex]:
- Substitute [tex]\( x = 2 \)[/tex] into the function [tex]\( g(x) \)[/tex]:
[tex]\[ g(2) = 1 - 2 \][/tex]
- Calculate the subtraction:
[tex]\[ 1 - 2 = -1 \][/tex]
So, [tex]\( g(2) = -1 \)[/tex].
3. Calculate [tex]\( (f - g)(2) \)[/tex]:
- To find [tex]\( (f - g)(x) \)[/tex], we subtract [tex]\( g(x) \)[/tex] from [tex]\( f(x) \)[/tex]:
[tex]\[ (f - g)(x) = f(x) - g(x) \][/tex]
- Substitute [tex]\( x = 2 \)[/tex]:
[tex]\[ (f - g)(2) = f(2) - g(2) \][/tex]
- Use the values we found:
[tex]\[ (f - g)(2) = 13 - (-1) \][/tex]
- Simplify the expression:
[tex]\[ 13 + 1 = 14 \][/tex]
Therefore, the value of [tex]\( (f - g)(2) \)[/tex] is [tex]\( 14 \)[/tex].
So, the correct answer is:
[tex]\[ 14 \][/tex]
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.